Analysis of Compliance with International Labour Law Standards on the Employment of Women in Cambodia, Vietnam, Laos and Thailand - Gumulak, Justyna (International Studies. Interdisciplinary Political and Cultural Journal, 2023)
This article presents international labour law standards on women’s employment and analyses their compliance in selected Southeast Asian countries: Cambodia, Vietnam, Laos and Thailand. Issues concerning equal rights in employment and maternity protection were discussed. The compliance of national regulations with the acquis of international labour law, particularly with the standards developed in the conventions of the International Labour Organization, was assessed. This article considers two areas of women’s employment. The first, related to gender equality, compares women’s and men’s salaries in the Southeast Asian countries in question and presents national laws prohibiting gender discrimination. The second develops issues related to maternity protection, such as the length of maternity leave, maternity allowance and breastfeeding breaks during work.